Primary adenosquamous cell carcinoma of the pancreas: the use of endoscopic ultrasound guided – fine needle aspiration to establish a definitive cytologic diagnosis - De Moura, Diogo Turiani Hourneaux (2018)
Pancreatic cancer is the second most common malignancy of the gastrointestinal tract in the US, and adenocarcinoma has been identified as the most common type of pancreatic cancer. Different types of pancreatic cancers have been classified: adenocarcinoma, ductal adenosquamous carcinoma, solid pseudopapillary tumors, endocrine neoplasms, acinar cell carcinoma, squamous cell carcinoma, cystic tumors, primary lymphoma of the pancreas, and metastatic lesions of the pancreas. Adenosquamous carcinoma is extremely rare, behave in a very aggressive way and is responsible for the 1 to 4% of the pancreatic exocrine neoplastic lesions. We describe the case of an 82-years-old African American female, presenting to our institution with quantifiable weight loss (12 kg in 3 months), jaundice and abdominal pain. On admission, laboratory tests were obtained: total bilirubin: 11.07 mg/dl with a direct fraction of 10.32 mg/dl. Cross-sectional abdominal CT scan with contrast, showed a lesion localized in the pancreatic head (hypodense on T1, measuring 3.5 x 3.5 x 2.5 cm), with vascular invasion of the portal vein. EUS showed a solid, hypoechoic, not well-defined lesion (measuring 3.98 x 3.80 cm), localized between the head and neck of the pancreas. EUS-FNA was performed with a 22G needle using the fanning technique. The cytological specimens demonstrated components of both squamous carcinoma and adenocarcinoma. The patient underwent ERCP procedure, and biliary drainage was performed with an entirely covered metallic stent placement. After a month from the procedures, the patient died due to the severity of the disease. Endoscopic ultrasound has proven to be the best method to diagnose solid pancreatic lesions, including rare and aggressive type of tumors like primary adenosquamous cell carcinoma that we described in this very interesting case report.